A Statistical Analysis of Bhairav-The first morning Raga (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
A raga, in Indian classical music, is a melodic structure with fixed notes and a set of rules characterizing a particular mood conveyed by performance. Bhairav is the first raga of the morning. The present paper gives a statistical analysis of this raga structure. Â